Development of Physics Teaching Materials with a Scientific Approach Loaded with Character Values in Fluid Material for Class XI IPA SMA - Amiruddin Supu; Maria Dafrosa Astri; Kadek Ayu Astiti; I Wayan Sukarjita (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
The purpose of this study is to design and develop physics teaching materials with a scientific approach that contain character values in fluid material for class XI science students, to find out the character values extracted from fluid materials, and to determine the results of the feasibility test of the teaching materials developed. This research uses the ADDIE development model. Religious, curiosity, discipline, social care, peace-loving, hardworking, independent, creative, caring for the natural environment, tolerance, responsibility, communicative, and honest are the character values extracted from the fluid aspects added to the teaching materials. The validity and practicality tests were conducted using a questionnaire instrument and analyzed using a Likert scale. The validity test was assessed by two material and media validators. Meanwhile, the practicality test was assessed by students of class X IPA SMA N 4 Kupang City, who were grouped into two, namely the small group test and the large group test. The results of the validity test of the material and media validators, respectively, obtained a percentage of 85.76% and 88.19% with very valid criteria. And the results of the practicality test based on the assessment of student responses to the developed teaching materials, namely the small group trial with a percentage of 88.03% and the large group test with a percentage of 89.17%, both of which included very practical criteria.